Основи методики суспільно-географічного дослідження особистих господарств населення - Богадьорова, Л.М. (Кримський науковий центр НАН України і МОН України, 2005)
Предложена методика общественно-географического исследования территориальной организации личных хозяйств населения. Разработаны подходы
оценки структуры, динамики, условий функционирования личных хозяйств, эколого-экономических и социальных проблем их развития. The methods of social-geographic investigation of the territorial organization
of the individual farms of the population were offered. The approaches of the structure
evaluation, dynamics of the terms of functioning of individual farms, ecological,
economic and social problems of their development were carried out.